Does Financial Performance Drive Environmental Disclosure and Environmental Cost? Evidence from Indonesia - Rini, Rima Kusuma; Adhariani, Desi (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 2 (2021), 2021)
This study aims to examine whether financial performance impact the environmental disclosure and environmental cost. Samples from mining and energy companies that are listed on the Indonesia Stock Exchange from 2015-2019 are analysed using content analysis method and ordinary least square regression. This study finds that the financial performance has a positive relationship to environmental cost that indicates assets are efficiently used as a basis to engage in spending on environmental activities. There is a negative relationship on the financial performance to environmental disclosure. Environmental cost to environmental disclosures proven has positive relationship. This study has an implication for wider stakeholder in understanding how financial performance affected environmental cost and environmental disclosure. This research implies the role of cost element in the relationship of financial performance and environmental disclosure.